Pre-laying sex differences in reproductive roles can constrain foraging behaviour in a monomorphic seabird - Katrina Siddiqi-Davies; Lewis Lancaster-Reeves; Joe Morford; Oliver Padget; Joe Wynn; Sarah Bond; Patrick Lewin; Paris Jaggers; Tim Guilford (Marine Biology, 2025)
Sex differences in foraging behaviour can arise in monomorphic species when reproductive roles differ. How these differences shape foraging behaviour during the pre-laying period—an understudied reproductive stage in seabirds—remains unclear. In a monomorphic procellariform seabird, the Manx shearwater ( Puffinus puffinus ), we compare foraging behaviour between sexes during pre- and post-laying periods. Prior to laying, sex roles differ, with females synthesizing the egg, while males are thought to primarily engage in nest defence. We found that pre-laying females take longer at-sea trips that are more distant from the colony, whilst males visit the colony more frequently, and undertake more dives. For males, pre-laying dives are shallower than those during the post-laying period. Sex differences largely diminish post-laying, as reproductive roles become more equivalent between sexes. We suggest that increased colony visitation during pre-laying may constrain males to closer foraging sites and these may be of poorer quality than those reached by females. We found that colony visitation appears to restrict evening foraging opportunities for males, as birds must commute to the breeding site for nocturnal visits. Our results show that significant differences in reproductive roles before egg-laying can constrain at-sea foraging behaviour. Understanding these differences can facilitate understanding of how sex-specific foraging behaviour may interact with human-induced changes in marine environments.